2010
DOI: 10.1001/archophthalmol.2009.394
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Studies of Conjunctival Nevi and Melanomas

Abstract: To evaluate the role of immunohistochemical methods in the diagnosis of benign and malignant conjunctival melanocytic proliferations.Design: Retrospective immunohistopathologic study.Methods: Paraffin-embedded tissue sections from 20 conjunctival nevi and 15 invasive melanomas were immunoreacted with antibodies against cellular antigens S-100 protein, MART-1, HMB-45, CD-45, and Ki-67 nuclear proliferation protein.Results: All nevi immunostained moderately to strongly for S-100 protein and MART-1. Results for H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
47
0
8

Year Published

2011
2011
2015
2015

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 44 publications
(95 reference statements)
2
47
0
8
Order By: Relevance
“…In a subsequent study, Keijser et al 24 concluded that Melan-A was a poor marker for conjunctival melanocytes, with 44% of conjunctival melanoma and 30% of PAM specimens showing negative antigenicity. Conversely, other studies 18,23,30 involving similar sample sizes concurred with our findings showing that both the intensity and the pervasiveness of Melan-A staining are stronger in conjunctival melanoma, PAM, and nevi than is S100 immunoreactivity.…”
supporting
confidence: 92%
See 4 more Smart Citations
“…In a subsequent study, Keijser et al 24 concluded that Melan-A was a poor marker for conjunctival melanocytes, with 44% of conjunctival melanoma and 30% of PAM specimens showing negative antigenicity. Conversely, other studies 18,23,30 involving similar sample sizes concurred with our findings showing that both the intensity and the pervasiveness of Melan-A staining are stronger in conjunctival melanoma, PAM, and nevi than is S100 immunoreactivity.…”
supporting
confidence: 92%
“…Chowers et al 22 initially evaluated Ki67 in PAM and found an approximately 3-fold increase in Ki67 reactivity with increasing atypia consistent with the outcomes of the present study. Jakobiec et al 18 similarly found increased Ki67 reactivity in conjunctival melanoma rather than in the overlying PAM within the same specimens. However, the usefulness …”
Section: Marker For Atypiamentioning
confidence: 83%
See 3 more Smart Citations